Terrigenous subsidies in lakes support zooplankton production mainly via a green food chain and not the brown food chain - Hirama, Fumiya; Urabe, Jotaro; Doi, Hideyuki; Kazama, Takehiro; Noguchi, Takumi; Tappenbeck, Tyler H.; Katano, Izumi; Yamamichi, Masato; Yoshida, Takehito; Elser, James J. (Frontiers in Ecology and Evolution, 2022)
Terrestrial organic matter (t-OM) has been recognized as an important cross-boundary subsidy to aquatic ecosystems. However, recent evidence has shown that t-OM contributes little to promote secondary production in lakes because it is low quality food for aquatic consumers. To resolve this conflict, we performed a field experiment using leaf litter as t-OM. In the experiment, we monitored zooplankton biomass in enclosures with and without addition of leaf litter under shaded and unshaded conditions and assessed food web changes with stable isotope analyses. We then examined whether or not leaf litter indeed stimulates lake secondary production and, if it does, which food chain, the detritus-originated food chain (“brown” food chain) or the algae-originated food chain (“green” food chain), contributes more to this increase. Analyses with stable isotopes showed the importance of t-OM in supporting the secondary production under ambient lake conditions. However, addition of the leaf litter increased the zooplankton biomass under unshaded conditions but not under shaded conditions. We found that phosphorus was leached from leaf litter at much faster rate than organic carbon and nitrogen despite its low content in the leaf litter. These results showed that leaf litter stimulated the increase of zooplankton biomass mainly through the green food chain rather than through the brown food chain, because the leaf litter supplied limiting nutrients (i.e., phosphorus) for primary producers. Our results indicate that the functional stoichiometry of the subsidized organic matter plays a crucial role in determining the relative importance of brown and green food chains in promoting production at higher trophic levels in recipient ecosystems.